Population Genetic Analysis Reveals a High Genetic Diversity in the Brazilian Cryptococcus gattii VGII Population and Shifts the Global Origin from the Amazon Rainforest to the Semi-arid Desert in the Northeast of Brazil. - Ana C P Souto; Lucas X Bonfietti; Kennio Ferreira-Paim; Luciana Trilles; Marilena Martins; Marcelo Ribeiro-Alves; Cau D Pham; Liline Martins; Wallace Dos Santos; Marilene Chang; Fabio Brito-Santos; Dayane C S Santos; et al. (Public Library of Science (PLoS), 2016)
Cryptococcus neoformans and Cryptococcus gattii are responsible globally for almost one million cryptococcosis cases yearly, mostly in immunocompromised patients, such as those living with HIV. Infections due to C. gattii have mainly been described in tropical and subtropical regions, but its adaptation to temperate regions was crucial in the species evolution and highlighted the importance of this pathogenic yeast in the context of disease. Cryptococcus gattii molecular type VGII has come to the forefront in connection with an on-going emergence in the Pacific North West of North America. Taking into account that previous work pointed towards South America as an origin of this species, the present work aimed to assess the genetic diversity within the Brazilian C. gattii VGII population in order to gain new insights into its origin and global dispersal from the South American continent using the ISHAM consensus MLST typing scheme. Our results corroborate the finding that the Brazilian C. gattii VGII population is highly diverse. The diversity is likely due to recombination generated from sexual reproduction, as evidenced by the presence of both mating types in clinical and environmental samples. The data presented herein strongly supports the emergence of highly virulent strains from ancestors in the Northern regions of Brazil, Amazonia and the Northeast. Numerous genotypes represent a link between Brazil and other parts of the world reinforcing South America as the most likely origin of the C. gattii VGII subtypes and their subsequent global spread, including their dispersal into North America, where they caused a major emergence.